Changes to simulated global atmospheric composition resulting from recent revisions to isoprene oxidation chemistry. (1st January 2021) - Khan, M. Anwar H.; Schlich, Billie-Louise; Jenkin, Michael E.; Cooke, Michael C.; Derwent, Richard G.; Neu, Jessica L.; Percival, Carl J.; Shallcross, Dudley E.
Abstract: Recent revisions to our understanding of the oxidation chemistry of isoprene have been incorporated into a well-established global atmospheric chemistry and transport model, STOCHEM-CRI. These revisions have previously been shown to increase the production and recycling of HOx radicals at lower NOx levels characteristic of the remote troposphere. The main aim of this study is to assess the resultant broader changes to atmospheric composition due to the recent revisions to isoprene oxidation chemistry. The impact of the increased isoprene-related HOx recycling is found to be significant on the reduction of volatile organic compounds (VOCs) lifetime, e.g. a decrease in isoprene's tropospheric burden by ~17%. The analysis of lifetime reduction of the potent greenhouse gas, methane, associated with the increased HOx recycling, suggests its significant lifetime reduction by ~5% in terms of the current literature. The revisions to the isoprene chemistry also reduce the amount of ozone (by up to 10%), but provide a significant increase in NO3 (by up to 30%) over equatorial forested regions, which can alter the oxidizing capacity of the troposphere. The calculated mixing ratios of formic acid are decreased which in turn leads to an increase in the inferred concentrations of Criegee intermediates due to reduced loss through reaction with formic acid (up to 80%) over the dominant isoprene emitting regions. Highlights: Isoprene-related HOx recycling reduce the lifetime of methane by ~0.5 years. The revised isoprene mechanism reduces tropospheric ozone by upto 10% over tropical forest region. The new isoprene mechanism reduces HCOOH levels which have a significant impact on Criegee intermediates loss in Amazon.